Current Trends in Web Engineering ICWE 2012 International Workshops MDWE, ComposableWeb, WeRE, QWE, and Doctoral Consortium, Berlin, Germany, July 23-27, 2012, Revised Selected Papers - Grossniklaus, Michael; Wimmer, Manuel (Information Systems and Applications, incl. Internet/Web, and HCI, 2012)
This book constitutes the thoroughly refereed post-workshop proceedings and the doctoral symposium of the 12th International Conference on Web Engineering, ICWE 2012, held in Berlin, Germany, in July 2012. The volume contains four workshops and a doctoral consortium, each focusing on specific research issues that contribute to the main themes of the ICWE conference: MDWE 2012: Eighth International Workshop on Model-Driven and Agile Engineering for the Web, ComposableWeb 2012: Fourth International Workshop on Lightweight Integration on the Web, WeRE 2012: Third Workshop on the Web and Requirements Engineering, QWE 2012: Third International Workshop on Quality in Web Engineering.